Fear-induced changes in breakfall kinematics for osoto-gari in novice judokas - Koshida, S.; Ishii, T.; Matsuda, T.; Hashimoto, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Awareness of the risk and incidence of injury during the breakfall movement may lead to a perceived fear, which could be detrimental to breakfall kinematics and may even increase the risk of judo-related head injuries. Therefore, our aim was to investigate the association between the perceived fear of the breakfall movement and breakfall kinematics for osoto-gari in novice judokas. Eight experienced and 10 novice judokas volunteered to participate in this study. Motion data of the breakfall for osoto-garl was collected using a three-dimensional motion analysis technique. We found a similar trend in the joint angle curve and peak neck extension momentum for novice judokas who perceived fear of the breakfall and for those who did not. The results indicate that perceived fear of the breakfall movement may not be associated with a novice judoka's breakfall motion skill for osoto-gari.